DEVELOPMENT OF A MODULE BASED ON RIAU LOCAL WISDOM ON NORMS IN MY LIFE MATERIAL FOR GRADE V ELEMENTARY SCHOOL STUDENTS: PENGEMBANGAN MODUL BERBASIS KEARIFAN LOKAL RIAU PADA MATERI NORMA DALAM KEHIDUPANKU UNTUK SISWA KELAS V SD - Gusrika Fauza Rofah; Zaka Hadikusuma Ramadan (SOSIOEDUKASI, 2025)
This research aims to develop a learning module based on Riau local wisdom on the material "Norms in My Life" for grade V students at SD Negeri 17 Pekanbaru, Riau Province, which is valid, practical, and effective. The school is located in an urban area with a strong local cultural diversity, but it is not yet fully reflected in the teaching materials used. The background of this research is the limited availability of relevant and contextual teaching materials, especially those that integrate the values of local wisdom, so that it has an impact on students' low understanding of the concept of norms in daily life. This research is a development research that adapts the ADDIE (Analysis, Design, Development) model to the development stage. The analysis stage includes the identification of teachers, students, and curriculum needs. The design stage includes designing structures, materials, and the integration of Riau's local cultural values. At the development stage, the validity test of the module was carried out by material experts, linguists, and learning design experts. Data was collected through interviews and validation questionnaires, then analyzed qualitatively and quantitatively. The results of the study show that the modules developed have met the eligibility criteria with a very high level of validity after going through a revision process based on expert input. The final validation score from the subject and language experts ranges from 92.5% to 95%, which indicates that the module is "very worth using without revision". Thus, this module is expected to be an innovative solution in increasing students' understanding of norms while fostering appreciation for the values of Riau's local wisdom.